GE_GERICHTE P/23170/2018 vom 19. Dezember 2018 - GE Cour de justice (2018)
CLASSEMENT DE LA PROCÉDURE ; IN DUBIO PRO DURIORE ; VOIES DE FAIT ; CAS BÉNIN ; DÉNONCIATION CALOMNIEUSE | CPP.310; CP.303; CP.125; CP.52